Analisis Kaidah Fiqhiyyah Bab Nikah Menurut Mazhab Imam Hanafi - Sinulingga, Achmad Yasir; Adly, Mhd Amar; Firmansyah, Heri (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This paper aims to find out how about the rules of كُلُّ لَفْظٍ وُضِعَ لِتَمْلِيْكِ العَيْنِ حَالًّايصِحُ بِهِ النِّكَاحُ, وَمَالَيْسَ كَذَالِكَ لَا يَصِحُ بِهِ وَكُلُّ مَنْ يَصْلُحُ اَنْ يَكُوْنَ قَابِلًا لِلعَقْدِ بِنَفْسِهِ يَنْعَقِدُ النِّكَاحُ بِشَهَادَتِهِ, وَكُلُّ مَنْ يَصْلُحُ اَنْ يَكُوْنَ وَلِيًّا فِي النِّكَاحِ يَصْلُحُ اَنْ يَكُوْنَ شَاهِدًا فِيهِ. in Islamic family law and how it is applied to Muslim communities in Indonesia. This research is a library study (library resecarh). Primary data sources are obtained by reading the literature related to the discussion of the rules in the marriage chapter. The results of the research show both in the Qur'an and Hadith that a lafazd that aims to own something then the ownership is valid with the contract in question, the intention of the purpose of a lafaz that determines the ownership of something. Meanwhile, the application of these rules in the Muslim community in Indonesia has long been practiced and has been transformed into KHI article 14 as a pillar and condition of marriage. It is hoped that in the future other fiqh rules can also be transformed into national law.